INNOVATIONS IN BIOREMEDIATION: HARNESSING MICROBIAL POWER TO CLEAN UP POLLUTION - Yang Xiang; Sun Wei; Elvis Ewane (Yayasan Adra Karima Hubbi, 2025)
Pollution poses a significant threat to ecosystems and human health, prompting the need for effective remediation strategies. Bioremediation, which utilizes microorganisms to degrade environmental pollutants, has emerged as a promising approach to address this challenge. This study aims to explore recent advancements in bioremediation technologies, focusing on the role of specific microbial communities in the degradation of various pollutants, including heavy metals, hydrocarbons, and pesticides. The research seeks to identify effective microbial strategies and their applications in real-world scenarios. A comprehensive literature review was conducted, analyzing recent studies on microbial bioremediation techniques. Laboratory experiments were performed to evaluate the degradation rates of selected pollutants by specific microbial strains. Case studies of successful bioremediation projects were also included to illustrate practical applications. Findings indicate that innovative microbial techniques, such as genetically engineered strains and bioaugmentation, significantly enhance the degradation of pollutants. Successful case studies demonstrated substantial reductions in pollutant concentrations, showcasing the efficacy of microbial bioremediation in various environments. This research highlights the potential of harnessing microbial power for effective pollution cleanup.